Outcomes of an aseptic technique for Kirschner wire percutaneous pinning in the hand and wrist. Issue 4 (April 2021) - Levy, Kenneth H.; Sedaghatpour, Dillon; Avoricani, Alba; Kurtzman, Joey S.; Koehler, Steven M.
Highlights: The tenets of our technique maximize the clinical benefits on K-wires in hand/wrist fractures while minimizing the concern for infection. Percutaneous K-wire fixations can safely and effectively fixate fractures of the hand/wrist in fixation periods exceeding 8 weeks. Exposed K-wires should not be bent in situ nor inserted through an incision for fixation of hand/wrist fractures. Percutaneous K-wires should be covered with a desiccant dressing to prevent pin site infections. Abstract: Introduction: Kirschner wires (K-wires) have been shown to effectively stabilize fractures of the hand and wrist, but are associated with high infection rates, which may limit its use. Previous literature has attributed the risk of infection to many different aspects of a fixation technique. However, we introduce an approach to percutaneous K-wire pinning to mitigate the risk of infection. Methods: Patients undergoing K-wire fixation procedures of the hand and wrist were retrospectively queried. All cases were performed under the same principles of our technique. None of the K-wires were buried, nor bent and were covered with betadine-soaked alcohol pads as pin site dressings. Pins were removed in an outpatient procedure room up to 12 weeks postoperatively and were then assessed for signs of superficial or deep infection. Results: 90 patients were included in this study across a variety of K-wire fixation operations in the hand and wrist. No patients presented with any signs of infection or other complications necessitating postoperative antibiotics, early pin removal, or reoperation. Discussion/Conclusion: The specific guidelines of our technique resulted in no cases of pin site infection, despite a largely underserved patient population. Our low incidence of infection was maintained without the use of prophylactic antibiotics and in patients with long periods of fixation. While the high infection rates in previous literature have often been associated with wires left exposed, the principles of our technique allow for K-wire fixations to be performed percutaneously without burying the wires. This may allow for improved cost and time efficiency, without compromising patient safety.